A influência da estrutura organizacional no desenvolvimento de um ambiente interno de inovação: um estudo de caso na 3M do Brasil - Gaspary, Eliana (2014)
The organizational structure and the internal environment are considered important predictors for the development of innovation in the organizational literature. Yet, few researches analyze the relation between these issues. Based on this gap we aimed throughout this study to better understand how the dimensions of the organizational structure influence on the development of an work environment for innovation in the area of research and development of the 3M Company in Brazil. The research methodology follows a descriptive and explanatory approach based on qualitative and quantitative data collection. A case study was used as the investigative method, which was carried out in a company well renowned for its innovative style: The 3M of Brazil. The data collection was taken through in depth interviews with eight managers, as well as the application of questionnaires to 39 collaborators of the company s corporative laboratory. The results obtained from the qualitative research show the company follows a matrix structure, decentralized, with a medium level of formalization and highly integrated. The internal environment is focused towards innovation with a number of policies and practices to encourage organization members and support leaders. There is integration and share of ideas among teams which are constantly challenged to break paradigms and innovate. People hold autonomy and freedom to perform their jobs; they have access to all necessary resources and have a strong sense of entrepreneurship reinforced by the company s innovative culture. The quantitative results of the research point out that some specific organizational structure dimensions influence the internal environment towards innovation. The results highlight that the level of communication influences positively leadership support and people s perception that resources implemented at work are sufficient. It was also observed that the level of formalization and standardization has a negative effect on encouraging leaders to innovate and on the level of challenges at work. Results also show the higher the centralization and hierarchy dependency the higher the pressure people feel performing their jobs. As the main study s implication we come to the fact that a work environment for innovation must be supported by more flexible organizational structures: decentralized structures that encourage autonomy and entrepreneurship; informal structures favoring people s freedom to execute their tasks; integrated structures that allow for a high level of communication flow and team diversity.